Characterization of Sr2Fe1.5Mo0.5O6-δ -Gd0.1Ce0.9O1.95 symmetrical electrode for reversible solid oxide cells. Issue 8 (1st June 2019) - Guo, Yangyang; Guo, Tianmin; Zhou, Shijie; Wu, Yujie; Chen, Hui; Ou, Xuemei; Ling, Yihan
Abstract: Development of reversible solid oxide cells (RSOCs) must face one major challenge of the poor reliability origination from the oxidization of Ni-based hydrogen electrode materials. In this work, Sr2 Fe1.5 Mo0.5 O6-δ -Gd0.1 Ce0.9 O1.95 (SFM-GDC) symmetrical electrode working both air and hydrogen electrode is designed and investigated for RSOCs. Regardless of the redox condition, SFM shows excellent structural stability by the XRD analysis and HR-TEM observation. Meanwhile, XPS analysis obviously demonstrates the co-existence of Fe 2+ /Fe 3+ and Mo 5+ /Mo 6+ couples, of which both proportions increase with the reduce oxygen partial pressure. Applying SFM-GDC symmetrical electrode, the 300 μm-thick YSZ electrolyte-supported RSOCs with GDC buffer layers show acceptance electrochemical performance, and switch smoothly between power generation and electrolysis modes with no obvious degradation after 20 h short-term stability working under humidified (∼3%H2 O) H2 and 3%H2 O-air atmospheres, respectively. Besides, the impedance spectrum were further studied using a relaxation time distribution function (DRT), and two polarization peaks (P1, P2) observed in the power generation mode shifted to the left at low frequency with the reduced temperature, while one more new polarization peak (P3) corresponds to the reaction gas diffusion owing to the low concentration steam (∼3% H2 O) in electrolysis mode. This research highlights that the stable and efficient SFM-GDC symmetrical electrode can be the potential RSOCs electrode candidates.